Evaluasi Program Lembaga Masyarakat Desa Hutan (LMDH) Dalam Menciptakan Hutan Lestari di Kecamatan Randublatung Kabupaten Blora Tahun 2010-2013 - Akbar Nur Imam Rhomadhona; Puji Astuti; Lusia Astrika (Journal of Politic and Government Studies, 2014)
AbstractSustainable forest management is a system of management of the forest resources while preserving the forest as well as attention to social conditions and welfare of the surrounding community or the community itself. In sustainable forest management, promoting maintaining environmental conditions or forest ecosystems such as flora and fauna as well as the water source. In sustainable forest management there are several parties involved in it, which involve Perhutani, social community, LMDH, as well as from external parties. LMDH itself was formed to as a bridge between the aspirations of the community forest with Perhutani. Perhutani act as policy and program makers to be executed in the system of sustainable forest management. Meanwhile, the external function is to provide empowerment training community already programmed by forestry. such as batik traning, snack made, and composting. In the Perhutani sustainable forest management and also LMDH own duty to make people aware of the importance of forest conservation. In order to achieve sustainable forest management need the cooperation of the parties involved so that later Perhutani obtain FSC certification for sustainable forest management. However, there are issues with its implementation faced the impact on the existence of programs that are not or have not been successfully executed. So we need to be able to improve program evaluation that will be made later.Program evaluation is assessing or measuring the extent to which a program or design that can be executed. Or it could mean that the judge or review the programs that have been carried out to find out what deficiencies or constraints of these programs and then find the solution, so that future programs can run on target.This research uses descriptive qualitative research method. The data collection techniques used to study the documentation and interviewing the parties involved, such as LMDH, society, and also Perhutani. LMDH and Perhutani as a key informant while supporting the community as informants.The results of the study explained that Perhutani and LMDH in creating a sustainable forest management system is realized through three aspects of sustainable forest management includes aspects of social management, production management aspects, and aspects of environmental management. As each of these aspects has its own program. That is from the aspect of social governance in the form of skills training programs to the community. socialization importance of forest conservation. from the aspect of environmental management programs will provide outreach to the public awareness of the environment by not using toxic pesticides, replaced with natural pesticides. From the aspect of production management / economics programinvolving the community in the process of forest production, and provide socialization regarding the obligation to use Personal Protective Equipment (PPE) in accordance with SOPs in production.Keywords: LMDH, Sustainable Forest Management, Perhutani, Evaluation